Grassland degradation-induced declines in soil fungal complexity reduce fungal community stability and ecosystem multifunctionality. (January 2023) - Luo, Shan; Png, G. Kenny; Ostle, Nicholas J.; Zhou, Huakun; Hou, Xiangyang; Luo, Chunling; Quinton, John N.; Schaffner, Urs; Sweeney, Christopher; Wang, Dangjun; Wu, Jihua; Wu, Yuwei; et al.
Abstract: Soil microorganisms are major regulators of ecosystem functioning and are under threat from human-induced disturbances. Among these threats is grassland degradation, which is estimated to affect 49% of the grassland area worldwide, threatening biodiversity and ecosystem functioning. Yet, we currently lack an understanding of how grassland degradation influences belowground microbial communities, their stability, and functioning, and how effective restoration efforts are for the recovery of these important belowground properties. Here, we assessed soil fungal network complexity and a suite of ecosystem functions along a well-characterised gradient of grassland degradation and restoration on the Qinghai-Tibetan Plateau, and conducted an accompanying microcosm experiment designed to test the effects of complexity on stability in soil fungal communities. We found that with increasing levels of grassland degradation, soil fungal communities became less complex and were less compositionally stable when confronted with drought under laboratory conditions. Moreover, this degradation-induced reduction in fungal community complexity was associated with lower ecosystem multifunctionality. However, fungal communities and ecosystem multifunctionality failed to recover even after ten years of grassland restoration. Our results indicate that degradation-induced simplification of fungal communities can potentially impair fungal community stability and ecosystem multifunctionality, thereby highlighting the need to protect and restore healthy grasslands with complex belowground microbial communities. Highlights: Grassland degradation resulted in less complex soil fungal communities, which were less stable when confronted with drought. Degradation-induced reduction in fungal community complexity was associated with lower ecosystem multifunctionality. Fungal communities and ecosystem multifunctionality failed to recover even after ten years of grassland restoration.